ChemInform Abstract: α‐Organylchalcogenation of Aldehydes and Ketones with Diorganyl Dichalcogenides Promoted by K3PO4. Issue 48 (2nd December 2014) - Movassagh, Barahman; Yousefi, Ali
Abstract Various aldehydes and ketones react with diorganyl dichalcogenides under mild reaction conditions leading to the corresponding α‐organylseleno and α‐arylthio carbonyl compounds.